Optimisation of Third Party Logistics Process in Freight Forwarding to Improved Efficiency - Mustika Sari; Bagus Ridwant Ramadhan; Iqbal Firmansyah; Sekar Widayastuti (Universitas Muhammadiyah Jakarta, 2025)
The study focuses on analyzing the product delivery preparation process within logistics companies to identify inefficiencies and propose actionable improvements. Using methods like Value Stream Mapping (VSM), Process Activity Mapping, and a fishbone diagram, the study aims to reveal the underlying causes of waste in the process. VSM was employed to visualize the entire flow of the delivery process, identifying areas where value is added and where waste occurs. The result is Process Activity Mapping classified activities into three categories: value-added, non-value-added, and necessary non-value-added. This categorization offers valuable insights into potential areas for improving efficiency. The Fishbone diagram further helped identify root causes of waste, focusing on inappropriate processing, excessive transportation, and delays as the main inefficiencies. The study concluded that these types of waste significantly hamper the effectiveness of the delivery activity, increasing costs and lead times. The study advocated for process simplification, optimization of transportation routes, and mitigation of delays via improved planning and coordination to augment operational efficiency and decrease costs in product delivery preparation